(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Wasted tyres have become a growing disposal problem throughout the world which is caused by increasing the number of vehicles on the roads. On the other hand, Karewa soils exhibit generally undesirable properties. They tend to have low strength, compressible, swell when wetted and shrink when dried. To overcome this problem, the present study is being conducted to investigate the effect of shredded scrap tires on the strength parameters of Karewa soils of Kashmir. In this thesis work, the shredded tire content taken is 0%, 2%, 4%, 6%, 8% and 10% by weight of soil and the size of shredded scrap tires taken is 10mm to 40mm in length and 10mm to 15mm in width. First the tests such as sieve analysis, specific gravity and Atterberg’s limits of Karewa soil has performed. To assess the behaviour of Karewa soils reinforced with shredded tyres, Proctor compaction test, CBR test and UCS tests were conducted. Test results show that due to the addition of shredded tyres to Karewa soil, the CBR value of soil increases continuously with the addition of shred tyres while its peak value was founded at 8% of shred tyres. At 8% addition of shredded tyres, its CBR value increases by 173.44% as compared to un-reinforced soil. The proctor compaction test results show that with the addition of shred tyres to soil, its Optimum Moisture Content (OMC) increases while Maximum Dry Density (MDD) decreases continuously. The Unconfined Compression test (UCT) results shows that with the addition of shred tyres, the unconfined compression strength increases upto 8% shred content and then declined at 10% shred content. Thus 8% is the optimum shred content at which both CBR and UCS shows better results as compared to unreinforced soil. The results have shown both numerically and graphically in this thesis work.